A qualitative investigation of perceptions towards antibiotics by members of the public after choosing to pledge as an Antibiotic Guardian - Lorna Flintham; Diane Ashiru‐Oredope; Jordan Charlesworth; Roger Harrison; Elizabeth Dalgarno (Wiley, 2023)
Abstract Introduction Antimicrobial resistance is one of the biggest threats facing global humanity. In 2014, Public Health England (now the UK Health Security Agency) launched the Antibiotic Guardian (AG) campaign as a national health promotion initiative to increase public and health professionals' commitment to reducing the threat of antibiotic resistance (ABR). The aim of this research study was to gain a snapshot of public AG attitudes towards antibiotic use, the AG campaign and illness postpledge. Methodology This research used an exploratory study design using thematic and framework analysis of semistructured, in‐depth interviews. A purposive convenience sampling strategy was used to recruit 10 participants; adults in the general population who had registered with and chosen an AG pledge via the AG online platform during November 2020 were eligible for inclusion. Interviews were conducted via Zoom. Results Six main themes were identified: campaign awareness, motivators to pledge (uncertainty about the future of ABR, personal gratification, personal responsibility, moral obligation and COVID‐19), perceptions of personal responsibility (and patient perspectives of moral obligation in clinicians), the impact of the campaign and campaign promotion. Pledging appeared to solidify existing perceptions AGs held. Behavioural motivations for responsible antibiotic behaviours stemmed from perceptions of personal responsibility, moral obligation and concerns about ABR. AGs attributed responsibility to variable patterns in overprescribing. Perceptions towards COVID‐19, coinciding with the previously established study period, appeared mixed. AGs were keen to promote responsible perceptions in relation to antibiotics, resistance and the AG campaign. However, poor social acceptability of ABR concern was raised as a barrier to campaign promotion. Discussion The AGs' longstanding commitment to antimicrobial resistance demonstrates the importance of a pre‐existing interest in the public's self‐reported judicious behaviours and decision to pledge to an ABR‐focused campaign. Presenting the local and global threat to human mortality and morbidity in a more relatable format in public messaging should be considered in future strategies promoting ABR awareness and shifts in public perceptions. More frequent messaging to existing AGs is further recommended to propagate positive behaviour change among a wider audience. Patient or Public Contribution This study was based on interviews with adult members of the public who had pledged to be AGs via the website www.AntibioticGuardian.com. Interviews were based on the public's perceptions of the AG campaign, antibiotic use and ABR.